Effect of Microstructural Changes during Annealing on Thermoelectromotive Force and Resistivity of Electrodeposited Ni85.8Fe10.6W1.4Cu2.2 Alloy. (31st May 2017) - Spasojević, M.; Maričić, A.; Vuković, Z.; Đukić, S.; Ribić-Zelenović, L.; Spasojević, M.
Abstract : Ni85.8 Fe10.6 W1.4 Cu2.2 alloy powder containing nanocrystals of an FCC-structured solid solution of iron, tungsten, and copper in nickel embedded in an amorphous matrix was electrodeposited from an ammonia citrate solution. The alloy exhibits thermal stability in the temperature range between 25°C and 150°C. Over the range 150−360°C, the alloy undergoes intense structural relaxation which considerably increases the electron density of states and, hence, its electrical conductivity. Less intense structural relaxation takes place at temperatures between 360°C and 420°C. In the temperature range of 420°C to 460°C, relatively more intense changes in the electron density of states at the Fermi level occur, as induced by the structural relaxation resulting from the stabilization of larger less mobile tungsten atoms and copper atoms. The large decrease in electrical resistivity and the high increase in the electron density of states at the Fermi level in the temperature range 460−520°C are due to amorphous matrix crystallization and FCC-phase crystal grain growth.